Entre le massif de l’Aurès et les oasis : apparition, évolution et disparition des communautés ibâḍites du Zâb (viiie-xive siècle) - Allaoua Amara (Revue des Mondes Musulmans et de la Méditerranée)
After spreading among the pastoral communities of Tripolitania, Ibâḍism was quickly disseminated in the Aurès mountains and even in the oasis of Northern Sahara. Under the influence of Hawwâra, Banû Birzâl, Miknâsa and Banû Kimlân tribes, all converted to this religious stream, the province called Zāb by the Arabic authors was transformed into an Ibâḍî stronghold. Nomadism, a dominant way-of-life in this area, contributed to the diffusion of this doctrine and to the integration of rural communities under the authority of the Imamate of Tâhart. However, half a century later the Ibâḍî communities of the Zâb were reorganised into two rival branches : Wahbism and Nukkârism. This new situation occurred in a context of growing proselytizing activity displayed by Shi‘î and Sunnî Malikî based in the local urban centers, and caused a military reply of Nukkârism under Abû Yazîd’s leadership. Threatened by the dynasties of Northern Maghrib, the Ibâḍî communities either disappeared or moved away from their territories to take refuge into the oasis of Northern Sahara. Their decrease in size was accelerated by the arrival of the Banû Hilâl, giving birth to a new socioreligious map of the region.